ANALYSIS OF TYPICAL TASIKMALAYA TRADITIONAL FOOD NAMES USING DESCRIPTIVE SEMANTIC THEORY - Neng ira Hoerunisa; Milna Lidia Sari; Putri Angel Lestari; Aveny Septi Astriani (Media Inovasi Pendidikan dan Publikasi, 2023)
Indonesia's territory stretches from Sabang to Merauke with various ethnic and cultural diversity. Including in the culinary field, every region of Indonesia has unique foods that have various shapes, types, textures and names that reflect local regional customs and culture. This research examines the names of traditional Tasikmlaya foods using semantic descriptions. Based on the results of this study, we obtain the origins of the names and find out the description of each traditional food, starting from the shape, taste and processing method until it is known by the wider community as a traditional Tasikmalaya food.